HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK DENGAN POLA MENSTRUASI PADA MAHASISWI JURUSAN OLAHRAGA UNIVERSITAS NEGERI MEDAN TAHUN 2014 - devi eni pohan; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Irregular menstrual cycle is an imbalanced hormone impact in women reproductive system. While imbalance of energy relates to estrogen reduction, disturbance of metabolism, and oligomenore as well as polimenore. Excessive physical activity also affects the menstrual cycle. The purpose of this research is to determine the relation between dietary habit and physical activity with menstrual pattern for student majoring sports in State University of Medan 2014. This is descriptive research using cross sectional design research. The population of this research is student of PJKR UNIMED of 2012, 2013, and 2014 batch. Technique of sampling is using proportional simple random sampling which involves 58 sampels (23 sampels of first grade, 20 sampels of third grade and 15 sampels of fifth grade). Dietary habits, menstrual pattern, and physical activity data gained after doing interview by using questionare. to measure dietary habits using food recall and food frequency questionare. Then data analized by using Chi Square test. The research results showed that student dietary habit of is at good category (56,9%). Student physical activity is at medium category (53,4%). Student menstrual cycle is irregular (51,7%). Based on Chi Square test, it is known that there is correlation between dietary habit (quantity) with menstrual blood volume (p=0,003). While there is no correlation between dietary habits and physical activity with menstrual cycle, long menstruation, and menstrual blood volume. It is recommended that student maintan their dietary habit and reproductive health as well by applying their diet in accordance with Guideline for Balanced Nutrition (GBN). Keyword : dietary habits, physical activity, menstrual pattern